2012
DOI: 10.1037/a0029098
|View full text |Cite
|
Sign up to set email alerts
|

When diagnosing ADHD in young adults emphasize informant reports, DSM items, and impairment.

Abstract: Objective This study examined several questions about the diagnosis of attention-deficit/hyperactivity disorder (ADHD) in young adults using data from a childhood-diagnosed sample of 200 individuals with ADHD (age M = 20.20 years) and 121 demographically similar non-ADHD controls (total N = 321). Method We examined the use of self-versus informant ratings of current and childhood functioning and evaluated the diagnostic utility of adult-specific items versus items from the Diagnostic and Statistical Manuel o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
240
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 216 publications
(259 citation statements)
references
References 43 publications
12
240
3
4
Order By: Relevance
“…Contrary to predictions, a significantly higher percentage (22%) of probands self-reported persistent ADHD than did comparison participants (2%). This persistence estimate is higher than those gleaned from selfreport in past longitudinal studies of both female and predominately male samples of young adults (e.g., Barkley et al, 2002;Babinski et al, 2011;Sibley et al, 2012).…”
Section: Effects Of Informant On Dsm-iv Adhd Persistencecontrasting
confidence: 40%
See 4 more Smart Citations
“…Contrary to predictions, a significantly higher percentage (22%) of probands self-reported persistent ADHD than did comparison participants (2%). This persistence estimate is higher than those gleaned from selfreport in past longitudinal studies of both female and predominately male samples of young adults (e.g., Barkley et al, 2002;Babinski et al, 2011;Sibley et al, 2012).…”
Section: Effects Of Informant On Dsm-iv Adhd Persistencecontrasting
confidence: 40%
“…Babinski and colleagues (2011) found that parents reported greater impairment than their daughters, particularly in the domain of intrafamily conflict; Barkley et al (2002) found that parent-reported ADHD status was associated with poorer outcomes on all eight of their study's outcomes, including such objective measures as employer performance ratings and school transcripts. Further, although Sibley et al (2012) found that parent-and self-report DSM-IV ADHD rates did not differ significantly (i.e., 12.0% and 9.6%, respectively), far higher percentages of parents than young adults reported clinically significant impairment (55.6% vs. 14.6%) and elevated symptom severity (71.8% vs. 24.4%).…”
Section: Effects Of Symptom Thresholds On Adhd Persistencementioning
confidence: 81%
See 3 more Smart Citations